GENDER BIAS IN THE JOURNALISM PROFESSION AGAINST WOMEN IN MEDAN CITY - Clara Adinda Salsabilla; Hasan Sazali (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to answer the following question: what forms and mechanisms of gender bias are experienced by female journalists in Medan, and how do these biases impact their roles and positions within the field of journalism? Employing a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that female journalists in Medan face systemic inequalities, including gender-based task segregation, male dominance in strategic editorial positions, and inadequate protection against harassment and workplace discrimination. Furthermore, prevailing social and cultural norms reinforce domestic expectations of women, which significantly restrict their mobility and career advancement in journalism. These findings affirm the relevance of structural feminist theory and the intersectionality framework, while offering practical contributions for the development of gender-responsive media policies. The study recommends revising internal media policies and strengthening advocacy networks to create a more equitable, inclusive, and discrimination-free professional environment for female journalists.